Pengaruh Kualitas Pelayanan Dan Kepercayaan Terhadap Kepuasan Nasabah (Studi Kasus Pada PT Bank Mandiri (Persero) Tbk. Cabang Tambun Mangunjaya) - Aldrias Satriady (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to determine the effect of Service Quality and Trust on Customer Satisfaction of PT Bank Mandiri (Persero) Tbk. KCP Tambun Mangunjaya. The sample of this research is the customer of Bank Mandiri Branch Tambun Mangunjaya. The sample used was 100 people using non-probability sampling technique with purposive sampling method. The results showed that partially the positive effect of the service quality variable on the customer satisfaction variable was β1 0.614 (sig 0.000) while the positive effect of the trust variable on the customer satisfaction variable was β2 0.400 (sig 0.028). The value of Adjusted R Square is 0.897, which means that 89.7% of service quality and trust affect customer satisfaction of PT Bank Mandiri (Persero) Tbk. KCP Tambun Mangunjaya and the remaining 10.3% were influenced by other factors not examined in this study.